Passion and Love (P/L) with Knowledge and Understanding (K/U): Coherence, Concurrence, Congruence and Coexistence of Passions and Knowledge in Human Mind - Ahamed, Syed V (Asian Journal of Interdisciplinary Research, 2020)
This paper deals with the development of personality in two parallel tracks as an infant evolves to be a unique individual in society. The primary track is based on the acquired knowledge that is appended to the genetic code or information that the infant inherits from both parents. This track is essential for survival and is the primary instinct to just live on from one moment to the next. It shapes a baby from an infant in the world, a child in a family, a person in a society. If this progression can be conceived as an evolutionary trail for the progress in an orderly fashion to enhance and grow in a knowledge domain, then a secondary, simultaneous and a parallel track also evolves to shape the emotions of the baby, the feeling of the child and the passion of the person. The feeling, emotions, and passions exist during every stage, however unperceived they might be. The baby smiles and cries, and is happy just as much as a child is joyful or sad, or is excited. As much as this parallelism exists, we extend the parallel evolution of the two tracks deep and prolonged into adulthood, maturity, and old age of the human being in the society. Whereas the knowledge trail enhances the child, adult, and mature human to become educated, knowledgeable, wise, and ethical, the passion trail deeply resident in the mind, makes the person (during all stages of life) realistic, honest, loving, and passionate.